Inconsistency between manganese superoxide dismutase expression and its activity involved in the degeneration of recognition function induced by chronic aluminum overloading in mice. (January 2016) - Qiu, H-M; Yang, J-X; Jiang, Q-S; He, D; Zhou, Q-X
Manganese (Mn) superoxide dismutase (SOD) is mainly located in mitochondrial matrix and is responsible for scavenging about 80% free radicals from oxidative and phospharylative process in mitochondria. It was reported that the insufficiency of Mn SOD expression or activity was connected to the development of neurodegenerative diseases. In this article, we investigated the time course related to the changes of Mn SOD expression and its activity from mouse brain as well as the recognition dysfunction in chronic aluminum (Al) overloading mice. Aluminum gluconate solution (equal to Al 400 mg/kg) was given to mice once a day, 6 days per week for 12 weeks via intragastric gavage. The learning and memory function, malondialdehyde (MDA) level as well as expression and activity of Mn SOD in cortex were determined. It was found that function of passive learning and memory and spatial recognition decreased, MDA level and Mn SOD expression increased during the period of chronic Al loading, but the Mn SOD activity rose from the 4th week and then decreased from the 8th week in cortex in Al overloading mice compared with the control. The results indicated that the inconsistency between Mn SOD expression and its activity might contribute to the development of recognition dysfunction induced by chronic Al overload.